2013
DOI: 10.32607/20758251-2013-5-2-90-99
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel IGF1R Kinase Inhibitors by Molecular Modeling and High-Throughput Screening

Abstract: The aim of this study was to identify small molecule compounds that inhibit the kinase activity of the IGF1 receptor and represent novel chemical scaffolds, which can be potentially exploited to develop drug candidates that are superior to the existing experimental anti-IGF1R therapeuticals. To this end, targeted compound libraries were produced by virtual screening using molecular modeling and docking strategies, as well as the ligand-based pharmacophore model. High-throughput screening of the resulting compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…First of all, the crystal structure of IGF-1R has been determined (73). Based on this structural information, the interactions between IGF-1R and small-molecule inhibitors are well defined, and extensive in silico molecular docking analyses have been carried out (74)(75)(76). Combining what is known about the well-defined interaction mechanism between small molecules and IGF-1R with our data pertinent to the penetration of PQ401 into Gram-positive bacterial lipid bilayers, it seems likely that it would be possible to eliminate the IGF-1R-inhibitory activity of PQ401 without the loss of its bacterial membrane-disrupting activity.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, the crystal structure of IGF-1R has been determined (73). Based on this structural information, the interactions between IGF-1R and small-molecule inhibitors are well defined, and extensive in silico molecular docking analyses have been carried out (74)(75)(76). Combining what is known about the well-defined interaction mechanism between small molecules and IGF-1R with our data pertinent to the penetration of PQ401 into Gram-positive bacterial lipid bilayers, it seems likely that it would be possible to eliminate the IGF-1R-inhibitory activity of PQ401 without the loss of its bacterial membrane-disrupting activity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to SHS, no previous study has reported antiviral activity for I-OMe-AG538, which was originally characterised as an insulin growth factor 1 receptor protein tyrosine kinase inhibitor [ 35 , 36 ]. This study establishes I-OMe-AG538’s credentials against the flaviviruses DENV, ZIKV and WNV for the first time, revealing it to be an interesting prospect for future development.…”
Section: Discussionmentioning
confidence: 99%
“…For 25 years, we have been participating in the Escape of virtual space by introducing approaches to the compounds widely exploited in HTS, sulfonamides, ureas, secondary amines, , to name a few. The key point of our research has been to deliver a simple, cost-effective, and highly feasible parallel chemistry.…”
mentioning
confidence: 99%